Caracterização químico-mineralógica de minérios de manganês - Alexandre Batista de Almeida (2010)
Manganese enjoys an important role in the metallurgy of steel, being an input of vital importance and still without similar equivalent. Due to the boom lived by the mineral sector in the last five years, especially in the years 2007 and 2008, the need of discovery of new sources of several minerals has become a main objective of several mining companies. In some cases, as for the iron ore, and manganese as well, studies were made on the economical viability for retreatment of the piles of mineral reject in some plants. With that new reality in the horizon, a methodology is needed to identify and to quantify the components of these new sources and, even in the already studied deposits, the use of fast, low-priced and efficient methodology is necessary. This work used four samples of manganese ores from the municipality of Congonhal/MG for the development of a routine of analyses capable of identifying the minerals present, of quantifying the most important elements and of characterizing their more outstanding properties, trying to offer an analytical route with reasonable cost and high reliability. The techniques of X-ray diffraction, X-ray fluorescence, thermal analysis, chemical analysis, specific surface area by the BET method and scanning electron microscopy were used in this work. The minerals identified by X-ray diffraction are confirmed by crossing their data with the results obtained by thermal analysis and ignition loss, where the presence of hydrated minerals is evident, both in the oxide phase and in the silicate phase, in the samples 01 and 02; on the other hand, in samples 03 and 04, only minerals with little or no hydration were identified. The results of the chemical analysis also show the concentration of the manganese in the oxide phase in the samples 01 and 02 and its distribution among oxide and silicate phases in the samples 03 and 04. The results of infrared spectrometry show the occurrence of hydrated minerals in the oxide phase, thus confirming the results of by X-ray diffraction, thermal analysis and ignition loss. The techniques used in this work have confirmed to be practical and capable of supplying reliable data, since these data have always been consistent